2002
DOI: 10.1095/biolreprod67.4.1327
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor as an Indicator of Sperm Function

Abstract: Expression of progesterone receptor (PR) localization on spermatozoa was determined in men with normal and abnormal spermiograms. Studies were also carried out to evaluate the potential of PR as a marker of sperm function. Progesterone receptor expression on spermatozoa from men with normozoospermia (n = 8), oligozoospermia (n = 7), asthenozoospermia (n = 8), oligoasthenozoospermia (n = 7), and teratozoospermia (n = 11) was analyzed using an immunocytochemical method with monoclonal antibodies against PR, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 54 publications
5
22
0
Order By: Relevance
“…32,33,35 Staining of mouse, stallion, and human spermatozoa with cellimpermeable fluorescein-tagged progesterone-BSA complex (P-FITC-BSA) revealed that progesterone receptors are masked by coating factors in freshly ejaculated sperm and become available after incubation under capacitating conditions, but only in a limited proportion of male gametes. 39,51,52 Similarly, in the present study, we obtained positive staining of progesterone receptors just for a fraction of sperm derived from B10.BR and B10.BR-Y del males. The sperm cells that were negative for P-FITC-BSA staining lack progesterone receptors or alternatively receptors in their membranes remained covered because of inefficient passing through the capacitating process.…”
Section: Discussionsupporting
confidence: 87%
“…32,33,35 Staining of mouse, stallion, and human spermatozoa with cellimpermeable fluorescein-tagged progesterone-BSA complex (P-FITC-BSA) revealed that progesterone receptors are masked by coating factors in freshly ejaculated sperm and become available after incubation under capacitating conditions, but only in a limited proportion of male gametes. 39,51,52 Similarly, in the present study, we obtained positive staining of progesterone receptors just for a fraction of sperm derived from B10.BR and B10.BR-Y del males. The sperm cells that were negative for P-FITC-BSA staining lack progesterone receptors or alternatively receptors in their membranes remained covered because of inefficient passing through the capacitating process.…”
Section: Discussionsupporting
confidence: 87%
“…Expression of progesterone receptor (PR) was observed on human sperms, and a strong correlation between PR expression and sperm function has been demonstrated 71 . Intriguingly, unlike estrogens, progesterone promotes the capacitated sperm to undergo acrosomal reaction 72 , 73 .…”
Section: Mechanisms Of Action On Spermatidsmentioning
confidence: 99%
“…Progesterone binds to the acrosome region of the sperm head (Gadkar et al 2002, Noguchi et al 2008Fig. 8Ac and Ad), although fluorescence of the middle piece of the sperm flagellum appears to be autofluorescence (Noguchi et al 2008;Fig.…”
Section: Binding Of 17be 2 To Hamster Spermatozoamentioning
confidence: 99%
“…Although spermatozoa do not have a classic intracellular progesterone receptor (PGR), a PGR is present in the cell membrane (Sabeur et al 1996, Baldi et al 1998, 2009, Lösel & Wehling 2003, Luconi et al 2004, Jang & Yi 2005. Moreover, it has been suggested that progesterone binds to the acrosome region, and PGR is localized to the same region in human (Gadkar et al 2002) and hamster spermatozoa (Noguchi et al 2008). Phospholipase C (PLC; Fukami et al 2003) and/or protein kinase A (Harrison et al 2000) are involved in progesteroneinduced AR.…”
Section: Introductionmentioning
confidence: 99%